Veríssimo passando Érico a limpo: espelhos e biblioteca em Solo de clarineta - Santos, Davi Siqueira [UNESP] (2015)
Érico Veríssimo gave to the brazilian literature library a large fictional work. However his last contribution is a book of memories in two volumes named Solo de clarineta. We could consider it as an imperfect end because his death, that was not the author's desire, is responsible for interrupting the active of the writer. Faced with this situation, aiming to develop a propositional theory, we subdivided our approach in three parts. The first gathers the family album and the travel album, trying to make an overflight that gets together some recordation of Érico about his life in the company of people and places. The second part focuses on the library of the author, with his readings of formations, his readings of confirmations and his own contributions in the bookcase of Brazilian literature. The third and last part tries to establish a comparison between the memory written and the fictional written. For this, using the mirror's metaphor, this thesis will try to approach things that are apart, that are separated by a reflective glass film, which we can call art speech. Through this division in three parts, the thesis tries to do a movement of tying the memorialist in the novelist. This way, our discussion sustain the argument that, in the end of his career, Veríssimo wanted to be transformed in a character of himself, trying with this to get the immortality, by literature, condition that his biological constitution couldn't provide